Antihyperglicemic and Antioxidant Potential of Aloe vera Juice Supplementation in the Type-II Diabetic Rats Model - Sufi Desrini; I.M. Kadek Dwi (Journal of Pharmacy and Nutrition Sciences, 2018)
To evaluate the potential effects of Aloe vera supplementation on blood glucose and antioxidant enzymes (Glutathione peroxidase, GPx; Superoxide dismutase, SOD) as well as lipid peroxides (Malondialdehyde, MDA) in the kidneys of experimental type-II Diabetic rats model. This was an experimental study with post-test only control group study design. Type-II diabetes rats were induced by streptozotocin (60 mg/kg, ip) and nicotinamide (230 mg/kg, ip) to Wistar rats. The diabetic rats were randomized into three groups, as follows: (i) Diabetic control rats (received CMC-Na 1 % vehicle only); (ii). Diabetic rats received glibenclamide 0,18 mg/200g orally once daily; (iii) diabetic rats group received glibenclamide (0,18 mg/200g body weight) as well as Aloe vera juice supplementation (3,6 mL/200 g body weight) orally once daily for 30 days. Rats fasted over night and the blood was withdrawn by retro-orbital puncture under light ether anesthesia on the pre-induction and 1st, 7th, 14th and 28th post induction to determine blood glucose. The kidney tissues of rats were taken under anesthesia at the end of 30 days. In the third group showed the decrease of blood glucose level significantly (p<0,05) compare to others. In addition to that, the third group has lower MDA levels and higher GPx and SOD enzyme levels compared to other groups (P<0,05). Aloe vera juice supplementation has antidiabetic and antioxidant potentials for type-II diabetes mellitus rats model being treated with standard medicine, glibenclamide.